Acquired Hemophilia A in a Female: A Case Report - Azis, Fahrul Abdul; Hardjianti, Tutik; Benyamin, Andi Fachruddin; Saleh, Sahyuddin; Minhajat, Rahmawati; Bayu, Dimas (Open Access Macedonian Journal of Medical Sciences, 2022)
INTRODUCTION: Coagulation factor deficit is a very uncommon hemostatic condition in which a single component or numerous factors are lacking. Hereditary coagulation factor defects are autosomal recessive, meaning that they can affect both men and women. However, hemophilia A, caused by lack of clotting factor VIII (FVIII), is an X-linked condition. Acquired hemophilia A (AHA) is a bleeding disorder caused by autoantibodies to FVIII. It should be distinguished from congenital hemophilia, an inherited disorder caused by a mutation in the FVIII gene. Here, we report the first known case in Indonesia, a 24-year-old female diagnosed with AHA. CASE PRESENTATION: A 24-year-old woman was referred to our facility for prolonged epistaxis. She had no previous history of extended menstrual flow or frequent epistaxis episodes, and there was no history of epistaxis or prolonged bleeding in her family. Bleeding time and prothrombin time were both normal, but time to activate partial thromboplastin was longer. The patient was diagnosed with AHA after von Willebrand disease (VWD) was ruled out. DISCUSSION: In some rare situations, females can be affected by X-linked illnesses such as hemophilia A and B. This may be due to a carrier mother or affected father, skewed X chromosome inactivation, Turner syndrome, inhibitory antibodies (acquired hemophilia), or a random mutation on the active X chromosome. In such instances, treatment is challenging. The usual treatment of choice is recombinant coagulation factors. CONCLUSION: Although VWD is the most frequent hereditary bleeding problem in females, other rare disorders such as AHA may be implicated. Clinicians should be aware of this when faced with patients that lack a history of bleeding disorders. Furthermore, AHA should be considered as a differential diagnosis in every female patient suffering from hemorrhage. Therefore, a comprehensive diagnostic approach is needed.